2008
DOI: 10.1016/j.jnoncrysol.2008.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Glass formation and glass transition in supercooled liquids, with insights from study of related phenomena in crystals

Abstract: Abstract.We divide glass and viscous liquid sciences into two major research areas, the first dealing with how to avoid crystals and so access the viscous liquid state, and the second dealing with how liquids behave when no crystals form. We review some current efforts to elucidate each area, looking at strategies for vitrification of monatomic metals in the first, and the origin of the property "fragility" in the second. Essential here is the nontrivial behavior of the glassformer thermodynamics. We explore t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 85 publications
1
75
0
3
Order By: Relevance
“…[9,38,89,90] As the glass transition is approached, viscosity diverges away from simple Arrhenius behavior but may be described using the Vogel-Fulcher-Tammann (VFT) equation…”
Section: Fig 5 the Macroscopic Shear Viscosity Of Aqueous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,38,89,90] As the glass transition is approached, viscosity diverges away from simple Arrhenius behavior but may be described using the Vogel-Fulcher-Tammann (VFT) equation…”
Section: Fig 5 the Macroscopic Shear Viscosity Of Aqueous Solutionsmentioning
confidence: 99%
“…[1,2] Changes in the degree and type of local structuring in water [3,4] may give rise to phenomena ranging from multiple crystalline phases to glass formation, and possible liquid-liquid phase transitions. [5][6][7][8][9][10][11] Recent studies on room temperature ionic liquids (RTILs [12,13]) have shown mesoscopic structure that is not liquid crystalline in origin. [14][15][16][17] Such RTILs may well form the micelle-like structure that is normally associated with amphiphilic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of the a-relaxation time (s a ) was modeled using the Vogel-Tamman-Fulcher (VTF) relationship of Eq. (1) (Chan et al, 1986;Angell et al, 1982;El Moznine et al, 2003;Angell, 2008).…”
Section: Dielectric Analysis (Dea)mentioning
confidence: 99%
“…As a glass-forming liquid is supercooled, its relaxation times and viscosity increase dramatically towards the glass transition (Angell et al, 1982). The temperature dependence of viscosity and relaxation times of amorphous materials above the glass transition can be described using the Vogel-Tammann-Fulcher (VTF) relationship (Angell, 1995(Angell, , 2002(Angell, , 2008Borde et al, 2002). Our previous studies (Silalai and Roos, 2010a,b) found a relationship between temperature dependence of a-relaxations and flow characteristics of milk powders above the T g and consequent dramatic changes in a-relaxations and stickiness occurred around the glass transition as a result of the increased molecular mobility and liquid bridging between particles (Silalai and Roos, 2010a,b).…”
Section: Primary Relaxations and Stickiness Of Milk Solidsmentioning
confidence: 99%
“…view of the glassy state (the "ideal glass-former" [161]) would emerge, as the understanding of crystallization kinetics would become irrelevant to the problem of understanding the existence of the glass transition. This could be regarded as an important research avenue.…”
Section: Figmentioning
confidence: 99%